Genetic polymorphisms and population genetic analyses of 57 autosomal InDel loci in Hubei Tujia group - Lan, Jiangwei; Zhang, Xingru; Cui, Wei; Mei, Shuyan; Xu, Jingtao; Zhu, Bofeng (Frontiers in Genetics, 2023)
Tujia is one of the 10 most populous ethnic groups in China, but the genetic structure has not been fully studied. In this study, we utilized 57 autosomal InDels to evaluate the genetic polymorphisms and efficiency of forensic applications in the Chinese Hubei Tujia group, and analyzed the genetic structure between the studied group with another 26 different groups from five continents in 1000 Genomes Projects (1KG) populations. The results showed that 57 InDels have no significant deviations from Hardy-Weinberg equilibrium and linkage disequilibrium tests. The combined power of discrimination (CPD) and the combined probability of exclusion (CPE) values for 57 InDels in Hubei Tujia group were 0.99999999999999999999999699822 and 0.999975177214539, respectively. In addition, the results of genetic structure analyses indicated that the Hubei Tujia group has close genetic relationships with the Chinese Han and the East Asian population. These 57 autosomal InDels can be used as reliable tools for forensic individual identification and paternity testing, and are more suitable for East Asian populations. Three InDels (rs72085595, rs145941537 and rs34529639) have the potential value for inferring ancestral information.